НОВЫЕ МУТАЦИИ В ГЕНЕ FBN1 У ПАЦИЕНТОВ С ВРОЖДЕННЫМ СМЕЩЕНИЕМ ХРУСТАЛИКА - Гусина, Ася Александровна; Сталыбко, Анастасия Сергеевна; Криницкая, Карина Александровна; Иванова, Валентина Федоровна; Румянцева, Наталья Владимировна; Кулак, Виктория Дмитриевна; Зубова, Татьяна Викторовна; Гусина, Нина Борисовна (Медицина: теория и практика, 2020)